Comparison of cortical bone thickness according to proinclination in skeletal Class I and Class II - Sierra-Ruelas , Patricia Sthefania (2025)
Objectives: To assess the cortical bone thickness of incisors when proclined and normo-positioned according to skeletal Class I and Class II malocclusions. Material and Methods: This study was descriptive, cross-sectional and observational. The study population consisted of 1220 pre-orthodontic treatment CBCT (Cone Beam Computed Tomography) scans from the archive of the Autonomous University of Nayarit between 2015–2023. The final sample included 76 scans. Inclusion criteria were as follows: diagnostic records containing CBCT scans of patients aged 12–40 years with no prior orthodontic treatment or anterior dental crowding. Incisor positioning was standardized for CBCT measurements. Data recording and descriptive statistics were performed using Microsoft Excel. Student’s t-tests were conducted using StatCalc software. Results: In the maxilla, both in Class I and II, when the incisors were in normal alignment or proclined, the average cortical thickness was greater than 1mm. However, in the mandible in Class II, when the incisors were proclined, most values were less than 1 mm.  Conclusions: When dental organs are proclined, the buccal cortical bone is thinner. In skeletal Class II with proclined lower incisors, the buccal cortical bone is thinner (<1 mm). CBCT allows the orthodontist to understand the biological limits within which they can work.